(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
This essay studies the acting epistemological operations in current argentinian critics of poetry, taking into account the theoretical-philosophical statement of its discourse. For that purpose, it postulates an emerging tradition located in the last decades of the 20th century, from the constitution of a foundational work: the essay by Noé Jitrik entitled “Alturas de Macchu Pichu. Una marcha piramidal a través de un discurso poético incesante”. Afterwards it was shown, by two eminent critics of the next generation —Cristina Piña and Daniel Freidenberg— the coexistence of opposite trends regarding aesthetics choices, typical of the poetics of the sixties, and continued to the eighties, but with the common feature, by the critics, of productive processing of modern literary theory.